Pengalaman Komunikasi Orang Tua dengan Anak Autis dalam Mendampingi Belajar di Rumah selama Pandemi Covid-19 - Nadya Rahma Aulia; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Differences in understanding between parents and autistic children arise due to the limited ability of children with autism to understand and use communication symbols, both verbal and nonverbal. This difference in ability causes barriers to communication. The effects of the COVID-19 pandemic have caused children with autism and their parents to experience challenges in carrying out learning at home. This study aims to describe communication patterns, communication experiences, and communication barriers experienced by parents with children with autism in assisting learning at home during the covid-19 pandemic. This study uses the basis of the Interaction Adaptation Theory by Judee Burgoon. This study uses a phenomenological method with data collection techniques in the form of in-depth interviews involving four parents who have autistic children at the elementary school education level. The results of this study indicate that the communication pattern created between parents and autistic children is a communication pattern as an interaction where parents dominate the role as message senders and autistic children tend to act as message recipients. Parents act as facilitators in assisting children to study at home. Parents explain the material with a delivery method that is easily understood by children with autism. Mother's informants tend to be more passive in following their children's will to study at home. Meanwhile, the father's informant was more enthusiastic and thorough in assisting children to study at home by finding solutions if children had difficulties. In communicating and interacting, autistic children experience psychological barriers that come from emotions that make it difficult to concentrate so it is difficult to receive messages conveyed by parents.